2008
DOI: 10.1055/s-2008-1080996
|View full text |Cite
|
Sign up to set email alerts
|

Endorectal Ultrasound: Its Role in the Diagnosis and Treatment of Rectal Cancer

Abstract: With development over the past 25 years of new surgical techniques and neoadjuvant therapy regimens for rectal cancer, physicians now have a range of treatment options that minimize morbidity and maximize the potential for cure. Accurate pretreatment staging is critical, ensuring adequate therapy and preventing overtreatment. Many options exist for staging primary rectal cancer. However, endorectal ultrasound (ERUS) remains the most attractive modality. It is an extension of the physical examination, and can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 55 publications
(104 reference statements)
1
26
0
Order By: Relevance
“…Restaging after neoadjuvant chemoradiation therapy is compromised by the effects of chemoradiation such as inflammation, edema, necrosis, and fibrosis. Postradiation changes such as fibrosis are difficult to distinguish from the residual tumor, and thus poor staging results mainly from overstaging [1,33]. ERUS-FNA allows cytologic examination of any suspicious lymph node or intramural mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restaging after neoadjuvant chemoradiation therapy is compromised by the effects of chemoradiation such as inflammation, edema, necrosis, and fibrosis. Postradiation changes such as fibrosis are difficult to distinguish from the residual tumor, and thus poor staging results mainly from overstaging [1,33]. ERUS-FNA allows cytologic examination of any suspicious lymph node or intramural mass.…”
Section: Discussionmentioning
confidence: 99%
“…It can be used to confirm malignancy in suspicious lesions as well as to identify and confirm nodal metastasis, tumor recurrence, or metastatic spread. Assessment of the depth of tumor penetration provides information for T staging in the TNM classification, and the ultrasonographic staging is suggested by the prefix ‘u’ [1]. For N staging, involvement is usually suspected if a lymph node is over 5 mm in diameter, round, and hypoechoic, features which may differentiate it from inflammatory nodes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Data from previous reviews and meta-analysis have shown similar rates of lymph node staging accuracy ranging from 60 to 74%, while the mean overall T correspondence was reported to be higher, that is, around 85% [4,12,13,14,15]. Our results suggest that the diagnostic yield of ERUS might have been overestimated.…”
Section: Discussionmentioning
confidence: 37%
“…This might have contributed to the overstaging, although we have not been able to fully assess this. [25][26][27] Puli et al performed a meta-analysis of 42 studies comprised of 5039 patients conducted between 1986 and 2008. 28 Their primary outcome was assessment of T-stage, where they demonstrated a pooled sensitivity of > 80% and a pooled specificity of > 90% for all T-stages.…”
Section: Discussionmentioning
confidence: 99%